Integrated Urban Water Resources Management - Hlavinek, Petr.; Kukharchyk, Tamara; Marsalek, Jiri.; Mahrikova, Ivana; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
Growing populations and rising standards of living exert stress on water supply and the quality of drinking water. In wastewater management, new challenges are caused by new chemicals of concern, including endocrine disrupters, pharmaceuticals, hormones, and personal care products, which often pass through wastewater treatment plants unabated, but may cause serious impacts on receiving aquatic ecosystems. Advanced wastewater treatment leads to production of biosolids, which are processed in various ways, including on-land applications in agriculture. Municipal effluents, combined with increasing withdrawals of water, lead to the worsening of receiving water quality. Expert opinions indicate that the only way to deal with the current urban water management dilemmas is by integrated management and innovative delivery of water services. This book presents important aspects of Challenges in Management of Urban Water Resources, Challenges in Urban Water Supply, Urban Drainage and Water Bodies, Wastewater Treatment and Security, and Wastewater Treatment and Reuse.
CHALLENGES IN MANAGEMENT OF URBAN WATER RESOURCES -- PROTECTION OF WATER RESOURCES IN THE SLOVAK REPUBLIC -- THE HUMAN DIMENSIONS OF IWRM: INTERFACES BETWEEN KNOWLEDGES AND AMBITIONS -- SUPPORTING THE SITING OF NEW URBAN DEVELOPMENTS FOR INTEGRATED URBAN WATER RESOURCE MANAGEMENT -- GIS FOR INTEGRATED WATER RESOURCES MANAGEMENT -- URBAN INFRASTRUCTURE MODELLING -- INTEGRATED URBAN WATER CYCLE MODELING -- WATER RESOURCES POLICY AND MANAGEMENT IN JORDAN -- URBAN WATER RESOURCES MANAGEMENT IN UKRAINE -- WATER SUPPLY, URBAN DRAINAGE AND WASTE WATER TREATMENT IN THE ORAVA REGION -- CHALLENGES IN URBAN WATER SUPPLY -- ROBUST DESIGN AND MANAGEMENT OF WATER SYSTEMS: HOW TO COPE WITH RISK AND UNCERTAINTY? -- AGEING AND RENEWAL OF URBAN WATER INFRASTRUCTURE -- BENCHMARKING OF WATER SUPPLY SYSTEMS - WATER LOSSES ASSESSMENT -- WATER SUPPLY OF BUCHAREST - PAST, PRESENT, FUTURE: A STUDY CASE -- WATER SUPPLY IN CITIES OF BELARUS: WATER QUALITY AND RISK ASSESSMENT -- RISK ASSESSMENT OF POTABLE WATER USED FROM RIVER INTAKES NEAR RADIATION-DANGEROUS OBJECTS (OBNINSK FOR ILLUSTRATION) -- URBAN DRAINAGE AND WATER BODIES -- WASTEWATER NETWORK CHALLENGES AND SOLUTIONS -- APPLICATION OF DECISION SUPPORT SYSTEM FOR SEWER NETWORK REHABILITATION -- IMPLEMENTATION OF FIBER OPTIC CABLES IN SEWAGE SYSTEM -- OVERVIEW OF URBAN DRAINAGE IMPACTS ON AQUATIC HABITAT -- URBAN RUNOFF - CONTAMINATION, PROBLEMS OF TREATMENT AND IMPACT ON RECEIVING WATER -- IMPACT OF ANTHROPOGENIC LOADS ON WATER QUALITY OF RIVERS OF THE UPPER AREAS OF OKA AND DESNA BASINS -- BIOSORBENTS IN SURFACE WATERS IN SITU TREATMENT AGAINST RADIONUCLIDES -- WASTEWATER TREATMENT AND SECURITY -- ECONOMIC AND TECHNICAL EFFICIENCY OF WASTEWATER PLANTS: A BASIC REQUISITE TO THE FEASIBILITY OF WATER REUSE PROJECTS -- JOINT OPTIMISATION OF SEWER SYSTEM AND TREATMENT PLANT CONTROL -- WASTEWATER TREATMENT IN BELARUS: PURIFICATION EFFICIENCY AND SURFACE WATER POLLUTION RISK -- WASTEWATER TREATMENT AND REUSE -- WATER REUSE IN CANADA: OPPORTUNITIES AND CHALLENGES -- INTEGRATED CONCEPTS FOR REUSE OF UPGRADED WASTEWATER - ROLE OF MEMBRANES IN WATER RECYCLING -- WATER REUSE FEASIBILITY STUDY IN THE CZECH REPUBLIC -- ALTERNATIVE FORMULATIONS FOR THE REUSE OF TREATED WASTEWATER IN MENEMEN PLAIN IRRIGATION SCHEME -- ASSESSMENT OF RAINWATER ROOF HARVESTING SYSTEMS FOR HOUSEHOLD WATER SUPPLY IN JORDAN -- WASTEWATER REUSE FOR IRRIGATION ON THE DESERT SANDY SOIL OF EGYPT: LONG-TERM EFFECT -- MEMBRANES FOR UNRESTRICTED WATER REUSE.
Keywords: ENVIRONMENTAL SCIENCES; SCIENCE (GENERAL).; CIVIL ENGINEERING; ENVIRONMENTAL POLLUTION; ENVIRONMENT; WASTE WATER TECHNOLOGY / WATER POLLUTION CONTROL / WATER MANAGEMENT / AQUATIC POLLUTION; CIVIL ENGINEERING; SCIENCE, GENERAL